PENENTUAN KONDISI TRANSFORMATOR BERDASARKAN KANDUNGAN GAS TERLARUT MENGGUNAKAN METODE SEGITIGA DUVAL - I M.T. Sismantara; W.G. Ariastina; A.A.N. Amrita (Program Studi Teknik Elektro UNUD, 2021)
Transformer failure may interrupt the electrical power delivery and causing a very highcost to the utility. In order to prevent failure in the transformer, continuous condition monitoringof a power transformer is necessary. Dissolved Gas Analysis (DGA) has been well knownmethod for transformer condition monitoring. A number of techniques have been developed inorder to assist engineers in interpreting the DGA test results. In this research, interpretation ofDGA test results using Fuzzy Logic approach based on Duval's Triangle is introduced. TheFuzzy Logic was developed based on the mapping of the different areas within the DuvalTriangle. The program validation was carried out by comparing the output program with thesimulated fault condition. The analysis results indicated that the introduced approach hassuccessfully determined the condition of the tested transformers. This approach, thus, wouldprovide advantages over the conventional method in determining the transformer condition.